MALAT1 recruited the E3 ubiquitin ligase FBXW7 to induce CRY2 ubiquitin‐mediated degradation and participated in trophoblast migration and invasion. Issue 3 (10th August 2020) - Wu, Lianzhi; Liu, Qian; Fan, Cuifang; Yi, Xiaofang; Cheng, Biheng
Abstract: This study aimed to investigate the mechanism by which MALAT1 regulates CRY2 expression and participates in trophoblast migration and invasion. Three patients with unexplained recurrent spontaneous abortion, four patients with missed abortion, and four women who underwent artificial miscarriages were enrolled in this study. Quantitative reverse‐transcription polymerase chain reaction and western blot analysis were used to detect RNA and protein expression, respectively. Trophoblast migration and invasion were detected by wound‐healing and transwell invasion assays. RNA pull‐down and Co‐IP assays were used to indicate the interaction between MALAT1 and FBXW7 or the interaction between FBXW7 and CRY2. The results showed significantly decreased MALAT1 expression in the villous specimens from the RSA patients relative to that in the villous specimens from the missed abortion patients and the normal villous specimens. MALAT1 promoted trophoblast cell migration and invasion by negatively regulating CRY2 protein expression. MALAT1 recruited FBXW7 to impair CRY2 protein stability. In conclusion, MALAT1 downregulation in trophoblasts might be related to miscarriage. MALAT1 may recruit the E3 ubiquitin ligase FBXW7 to induce CRY2 ubiquitin‐mediated degradation and participate in trophoblast migration and invasion. Abstract : MALAT1 downregulation in trophoblasts might be related to miscarriage. MALAT1 may recruit the E3 ubiquitin ligase FBXW7 to induce CRY2 ubiquitin‐mediated degradation and participate in trophoblast migration and invasion.